Two new species of Proceratophrys Miranda-Ribeiro, 1920 (Anura; Odontophrynidae) from the Atlantic forest, with taxonomic remarks on the genus - Dias, Pedro Henrique Dos Santos; Amaro, Renata Cecília; de Carvalho-E-Silva, Ana Maria Paulino Telles; Rodrigues, Miguel Trefaut (Zootaxa, 2013)
We describe two new species of Proceratophrys allied to the P. appendiculata species complex by the presence of single and long palpebral appendages and a triangular rostral appendage. Proceratophrys izecksohni sp. nov. is characterized by having small to medium size (SVL 32.1–54.2 mm in males), elongated hindlimbs (thigh length plus tibia length corre-sponding to more than 90% of snout-vent length), a broad head (head width corresponding to 55% of the snout-vent length), and by the light brown gular region and a cream colored ventral surface with scattered brown dots. Proceratophrys belzebul sp.nov. is characterized by its medium size (SVL 40.5–51.3 mm in males), by the absence of contact between the nasals bones and between the nasals and frontoparietals, by a very reduced iliac projection, by having frontoparietal bones very depressed and broad rostrally, by the smooth surface of the squamosal and nasal, by shallow, inconspicuous ventral pits on the maxillae, and by the females presenting the gular region dark brown. The two new species were previously confused with P. appendiculata for which we provide a new diagnosis. A molecular analysis based on mitochondrial and nuclear genes recovers a monophyletic Proceratophrys with high support, and the two new species in a clade with P. ap-pendiculata and P. tupinamba. The data also reinforce the idea that the species groups presently admitted to the genus are not monophyletic.